IMPLEMENTASI KETERAMPILAN PROSES SAINS PADA SISWA KELAS III SDN TRIWUNG KIDUL II KOTA PROBOLINGGO - Raudhatul Jannah; Ludfi Arya Wardana; Shofia Hattarina; Ribut Prastiwi Sriwijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of science process skills (SPS) among third-grade students at SDN Triwung Kidul II, Probolinggo City. The study used a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. The results indicate that the implementation of SPS was carried out through simple experiments, group discussions, and direct observation. Students became more active in learning and trained in critical and analytical thinking. However, the implementation of SPS still faced obstacles such as limited teaching aids, learning time, and student readiness. In conclusion, the implementation of SPS at this school is progressing quite well, although improvements to facilities, teacher training, and more innovative learning strategies are needed.